Hemophilia A Inhibitor Subjects Show Unique PBMC Gene Expression Profiles That Include Up-Regulated Innate Immune Modulators - Karim, Ahmad Faisal; Soltis, Anthony R.; Sukumar, Gauthaman; Königs, Christoph; Ewing, Nadia P.; Dalgard, Clifton L.; Wilkerson, Matthew D.; Pratt, Kathleen P. (Frontiers in Immunology, 2020)
The formation of pathological anti-FVIII antibodies, referred to as “inhibitors” affects up to 1/3 of severe Hemophilia A (HA) patients. “Immune Tolerance Induction” (ITI), enables 2/3 of treated patients to achieve peripheral tolerance to FVIII. Inhibitor formation is a classical T-cell dependent adaptive immune response. As such, it requires help from the innate immune system. However, the roles of innate immune cells and mechanisms of inhibitor development versus peripheral tolerance, achieved with or without ITI therapy, are not well understood. To address these questions, temporal transcriptomics profiling was carried out for FVIII-stimulated peripheral blood mononuclear cells (PBMCs) from the following groups of blood donors (40 total): (A) HA with a past inhibitor; (B) HA with a current inhibitor; (C) HA with no inhibitor history; (D) non-HA. PBMCs were stimulated with 5 nM FVIII, and total RNA was isolated 4, 16, 24 and 48 hours following stimulation. Time-series differential expression analysis was performed with DESeq2 followed by clustering and gene ontology (GO) analysis. Subjects in Groups A, B, C and D showed differential expression of 15, 56, 195 and 63 genes, respectively. A clustering analysis of Group B identified 3 distinct clusters. Interestingly, GO enrichment analysis revealed enrichments for innate immune modulators including NLRP3, TLR8, IL32, CLEC10A and COLEC12. NLRP3 and TLR8 are associated with enhanced secretion of the pro-inflammatory cytokines IL-1beta and TNF-alpha, while IL32, which has several isoforms, has been associated with both inflammatory and regulatory immune processes. Expression levels were validated by RT-PCR, ELISAs and flow cytometry. Group C temporal profiles fell into 4 distinct clusters. GO enrichment analysis revealed biological processes related to epithelial cell proliferation, responses to toxic substances, and positive/negative regulation of cytokine secretion (TNF, NQO1, PMEPA1). Group D temporal profiles fell into 4 distinct clusters. GO analysis identified expression patterns associated with leukocyte-mediated immunity, T-cell activation, and a hypoxia response. The inflammatory status of HA patients suffering from an ongoing inhibitor clearly includes up-regulation of innate immune modulators, some of which may act as ongoing danger signals that influence the responses to, and eventual outcome of, ITI therapy.